Mutations in LRP5 cause primary osteoporosis without features of OI by reducing Wnt signaling activity - Korvala Johanna; Jüppner Harald; Mäkitie Outi; Sochett Etienne; Schnabel Dirk; Mora Stefano; Bartels Cynthia F; Warman Matthew L; Deraska Donald; Cole William G; Hartikka Heini; Ala-Kokko Leena; et al. (BMC, 2012)
Abstract Background Primary osteoporosis is a rare childhood-onset skeletal condition whose pathogenesis has been largely unknown. We have previously shown that primary osteoporosis can be caused by heterozygous missense mutations in the Low-density lipoprotein receptor-related protein 5 (LRP5) gene, and the role of LRP5 is further investigated here. Methods LRP5 was analyzed in 18 otherwise healthy children and adolescents who had evidence of osteoporosis (manifested as reduced bone mineral density i.e. BMD, recurrent peripheral fractures and/or vertebral compression fractures) but who lacked the clinical features of osteogenesis imperfecta (OI) or other known syndromes linked to low BMD. Also 51 controls were analyzed. Methods used in the genetic analyses included direct sequencing and multiplex ligation-dependent probe amplification (MLPA). In vitro studies were performed using luciferase assay and quantitative real-time polymerase chain reaction (qPCR) to examine the effect of two novel and three previously identified mutations on the activity of canonical Wnt signaling and on expression of tryptophan hydroxylase 1 (Tph1) and 5-hydroxytryptamine (5-Htr1b). Results Two novel LRP5 mutations (c.3446 T > A; p.L1149Q and c.3553 G > A; p.G1185R) were identified in two patients and their affected family members. In vitro analyses showed that one of these novel mutations together with two previously reported mutations (p.C913fs, p.R1036Q) significantly reduced the activity of the canonical Wnt signaling pathway. Such reductions may lead to decreased bone formation, and could explain the bone phenotype. Gut-derived Lrp5 has been shown to regulate serotonin synthesis by controlling the production of serotonin rate-limiting enzyme, Tph1. LRP5 mutations did not affect Tph1 expression, and only one mutant (p.L1149Q) reduced expression of serotonin receptor 5-Htr1b (p < 0.002). Conclusions Our results provide additional information on the role of LRP5 mutations and their effects on the development of juvenile-onset primary osteoporosis, and hence the pathogenesis of the disorder. The mutations causing primary osteoporosis reduce the signaling activity of the canonical Wnt signaling pathway and may therefore result in decreased bone formation. The specific mechanism affecting signaling activity remains to be resolved in future studies.